Toksisitas Merkuri (Hg) Pada Penambang Emas di Nagari Koto Tuo Sijunjung Sumbar - Herix Sonata MS; Merry Thressia; Dewi Yudiana Shinta (SEHATI: Jurnal Kesehatan, 2021)
Gold processing by amalgamation produces gold amalgam and waste mercury. Poor mercury waste management can pollute the environment. Ilegal gold miners are often found in West Sumatra. In the process of gold processing always use Hg for the purification of the gold. This study aims to determine the level of mercury (Hg) in the gold miner's urine and see the long-working relationship. Mercury (Hg) is a heavy metal grouped into groups having high toxicity levels. The use of mercury (Hg) in the gold processing process can cause negative impact. Determination of mercury (Hg) with Atomic Absorption Spectrophotometer (SSA) method. The population of this research is gold miner worker in Nagari Koto Tuo Sijunjung as many as 3 people and also as sample. The instrument used in this research is a questionnaire and testing of urine specimen dilaboratorium with wet destruction method in research in.i Factors studied are the characteristics of r0espondents including age, and length of work. Sampling was done as much as 20 ml of urine. Urine sample examination was done at Laboratory by using Wet Destruction method. The result of mercury (Hg) examination in gold miner's urine was obtained by an average of 15.8 Î¼g / l Mercury (Hg) in urine with a threshold of 4 Î¼g / l. The benefit of this research is to provide an overview of the level of toxicity that occurs due to gold mining in illegal gold miners in Nagari Koto Tuo Sijunjung, West Sumatra.